Restaurer ou refaire ? Une étude sur White Rock Line et son devenir - Marie-Hélène Breuil; Agathe Houvet; Marie-Emmanuelle Meyohas (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The study of White Rock Line, an artwork by Richard Long dating from 1990, was entrusted to us in December 2011 by the CAPC, museum of contemporary art in Bordeaux. This was a first, comparative, study, looking at two possible options, restore or remake. In addition, the feasability and costing of the operations on work comprising 18 tonnes of stone 40 metres in length was necessary. This study used a sample of around ten original stones and the same number of newly harvested ones, with cleaning tests followed by « laboratory » experiments on the persistance and traces of the active products.